Basophils Trigger Fibroblast Activation in Cardiac Allograft Fibrosis Development. Issue 9 (28th March 2016) - Schiechl, G.; Hermann, F. J.; Rodriguez Gomez, M.; Kutzi, S.; Schmidbauer, K.; Talke, Y.; Neumayer, S.; Goebel, N.; Renner, K.; Brühl, H.; Karasuyama, H.; Obata‐Ninomiya, K.; et al.
Abstract : Fibrosis is a major component of chronic cardiac allograft rejection. Although several cell types are able to produce collagen, resident (donor‐derived) fibroblasts are mainly responsible for excessive production of extracellular matrix proteins. It is currently unclear which cells regulate production of connective tissue elements in allograft fibrosis and how basophils, as potential producers of profibrotic cytokines, are involved this process. We studied this question in a fully MHC‐mismatched model of heart transplantation with transient depletion of CD4 + T cells to largely prevent acute rejection. The model is characterized by myocardial infiltration of leukocytes and development of interstitial fibrosis and allograft vasculopathy. Using depletion of basophils, IL‐4–deficient recipients and IL‐4 receptor–deficient grafts, we showed that basophils and IL‐4 play crucial roles in activation of fibroblasts and development of fibrotic organ remodeling. In the absence of CD4 + T cells, basophils are the predominant source of IL‐4 in the graft and contribute to expansion of myofibroblasts, interstitial deposition of collagen and development of allograft vasculopathy. Our results indicated that basophils trigger the production of various connective tissue elements by myofibroblasts. Basophil‐derived IL‐4 may be an attractive target for treatment of chronic allograft rejection. Abstract : In a model of chronic cardiac allograft rejection, Schiechl et al show that graft‐infiltrating basophils contribute to the development of allograft vasculopathy and fibrosis in an interleukin‐4–dependent manner.